A Study on Diversity and Distribution of Figs (Ficus, Moraceae) in Bogor City, West Java, Indonesia - Ibnul Qayim; Tatik Chikmawati; Peniwidiyanti Peniwidiyanti (Journal of Tropical Biodiversity and Biotechnology, 2022)
Ficus (Moraceae) is a keystone resource species in the tropical region, and it contributes significantly to Bogor City's vegetation composition. Ficus spp. provide habitat for urban animals and contribute to providing environmental services for the community. Minimum data distribution and increasing land-use change possibly decrease Ficus diversity in Bogor City. This study aimed to analyse the diversity and distribution of Ficus spp. in Bogor City. The research was conducted by dividing Bogor City into 128 plots sized 1 x 1 km. Relative abundance and distribution analysis used QGIS version 3.10.2-A Coruña. A total of 37 species of Ficus spp. from six subgenera were found in Bogor. The highest distribution is mainly located around the Bogor Botanic Gardens and the Ahmad Yani City Forest in a tree and hemiepiphyte. Ficus benjamina and Ficus septica were the most common species found and spread throughout Bogor City. The significant land-use change in Bogor City has resulted in Ficus spp. generally spread in the northern and central parts. In contrast, in the southern part, they are relatively low. Some Ficus can also be bioindicators because they have growing habitats that tend to be specific and spread in certain areas. The presence of the Bogor Botanic Gardens has an important role in increasing the diversity of Ficus spp. in Bogor City.